1959
DOI: 10.1002/pol.1959.1203813410
|View full text |Cite
|
Sign up to set email alerts
|

The polymerization of acrylamide initiated by ceric nitrate‐3‐chloro‐1‐propanol redox systems

Abstract: The polymerization of acrylamide initiated by ceric nitrate and 3‐chloro‐1‐propanol was studied in aqueous solution at 25°C. At constant hydrogen ion and nitrate ion concentration, the rate of polymerization was found to be independent of the ceric ion concentration. The molecular weight of the polymer was very low. To explain the data, a kinetic scheme is proposed whereby ceric ions are responsible for both initiation and termination. The rate constant for oxidative termination was found to be of the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(49 citation statements)
references
References 8 publications
2
47
0
Order By: Relevance
“…In this work, grafting onto cellulose has been carried out in the presence of 4-VP with CAN as a redox initiator. Ceric ions are known to form complexes with various functional groups 17,18 that undergo decomposition by one electron-transfer mechanism to produce free radicals, by which the grafting of the appropriate monomer takes place. The presence of radicals on the cellulose backbone has been confirmed by electron spin resonance measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, grafting onto cellulose has been carried out in the presence of 4-VP with CAN as a redox initiator. Ceric ions are known to form complexes with various functional groups 17,18 that undergo decomposition by one electron-transfer mechanism to produce free radicals, by which the grafting of the appropriate monomer takes place. The presence of radicals on the cellulose backbone has been confirmed by electron spin resonance measurements.…”
Section: Resultsmentioning
confidence: 99%
“…graft copolymers of vinyl monomers such as acrylonitrile, methylmethacrylate, acrylic or acrylamide [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Water-soluble polymers containing amine, hydroxyl, carboxyl or dicarboxylic end groups by using redox initiator system were synthesized [18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…It is observed that with increased initiator concentration, the degree of grafting increased, attained a maximum and then decreased. This is due to increase concentration of initiator reacts with polymer radical and stops growth without bringing about transfer of electrons [7]. The grafting efficiency decreased steadily with increase in the initiator concentration.…”
Section: Effect Of Initiator Concentrationmentioning
confidence: 96%
“…The pH of chelate solutions were adjusted by PW9409 pH Meter using sodium hydroxide (free from carbonate) and hydrochloric acid. The stock solutions of ASTA and FeCl 3 were standardized [7,8]. The Fe(III) solutions were mixed with ASTA solutions, both in predetermined concentrations for executing molar ratio, continuous variation and slope ratio methods [4,5,9].…”
Section: 'Introductionmentioning
confidence: 99%